Generation and Subsequent Transport of Landslide-driven Large Woody Debris Induced by the 2018 Hokkaido Eastern Iburi Earthquake - Koi, Takashi; Hotta, Norifumi; Tanaka, Yasutaka; Katsura, Shin’ya (Frontiers in Earth Science, 2022)
The earthquake that occurred on September 6, 2018, in the eastern part of the Iburi region of Hokkaido, Japan (the Hokkaido Eastern Iburi Earthquake) caused thousands of shallow landslides in mountain areas. In areas where many landslides occurred, the trees on the slope became large woody debris (LWD) and were supplied to the catchment. Understanding the properties of LWD during the earthquake and its subsequent movement after the earthquake are important to manage the produced LWD and implement disaster prevention measures. This study evaluates the risk of future LWD disasters based on the sequence of LWD generation, its spatial distribution, and LWD relocation linked to temporal fluctuations in rainfall events. The study site is the upper Habiu River catchment (0.37 km2), where multiple shallow earthquake-related landslides occurred. Orthophotos and elevation data acquired before and after the earthquake were used to detect the properties of LWD. To evaluate the risk of an LWD disaster, we examined the correspondence between the hydraulic quantities, including the precipitation for 2 years after the earthquake and the water depth. It was estimated that approximately 7,000 LWD pieces were produced during the earthquake. Orthophoto interpretations indicate that over 80% of the LWD produced at the time of the landslide moved from the slope to the channel accompanied by the landslide debris; some of that then flowed down, accumulated, and formed logjams. In the river channel approximately 2 years after the earthquake, the destruction of logjams and the clear and drastic movement of LWD could not be confirmed. In this catchment, the uneven LWD distribution and the formation of logjams were fixed almost immediately after the landslide at the time of the earthquake; these characteristics are important when considering future actions. The water depth evaluation based on the difference in the excess return period indicate that the degree of risk differs depending on the deposition location in the channel. This suggests that not all LWD in the catchment are dangerous and that a risk assessment focusing on the LWD location can be effective. This study also makes it possible to determine high priority areas for LWD treatment.